Epidemiological Study of Sleep Apnea Prevalence and Associated Risk Factors in a Large Patient Population - Nihar Gami; Krutarth Shukla; Ishan Patel; Nayan Manish Gandhi (Wolters Kluwer Medknow Publications, 2024)
Background: Significant morbidity and death are linked to sleep apnea (SP), a prevalent sleep disease. For successful management, it is essential to comprehend its prevalence and the risk factors that are linked with it. The purpose of this study was to look at the prevalence of SP in a large patient group that was visiting a tertiary care facility and to discover risk variables that are connected with it. Methods: 500 volunteers were gathered from a tertiary care center to participate in cross-sectional research. Polysomnography, clinical evaluations, and standardized questionnaires were utilized to diagnose SP and gather pertinent information. A statistical study was conducted to evaluate the correlation between different risk factors and SP. Results: 35% of people had SP, with men between the ages of 40 and 60 having a greater frequency. It has been determined that smoking, obesity, and high blood pressure are important risk factors for SP. Compared to those with mild or moderate SP, individuals with severe SP had greater rates of smoking, hypertension, and obesity (BMI > 30). Conclusion: This study emphasizes how common SP is in tertiary care settings and how it is linked to smoking, obesity, and hypertension. Improving patient outcomes and lessening the impact of SP need early identification and management techniques that address these modifiable risk factors.